Cost-effectiveness of tuberculosis infection screening and treatment among high-tuberculosis risk immigrants and asylum seekers in The Netherlands: a cohort modelling study - Hontelez, Jan; Spruijt, Ineke T.; Bakker, Roel; Cobelens, Frank; Erkens, Connie; van den Hof, Susan; Vlas, Sake J. de (Journal of infection and public health, 2025)
Background - We evaluated the cost-effectiveness of TB infection (TBI) screening and TB preventive treatment (TPT) for immigrants, asylum seekers, and settled migrants in The Netherlands. - Methods - We used a deterministic cohort model that captures the natural history of TBI and TB disease for a migrant cohort in the country of origin (pre-entry) and in The Netherlands (post-entry). We fitted the pre-entry force of infection to Interferon Gamma Release Assay (IGRA) positivity rates from an implementation pilot study, and chest X-ray (CXR) positivity from the national entry-screening programme. We compared the costs per quality adjusted life year (QALY) gained for TBI screening with CXR screening over a 20-year time-horizon, accounting for parameter uncertainty by producing predictions for over 1000 unique parameter combinations that fit the data. - Results - TBI screening uniformly resulted in an increase in QALYs gained compared to current CXR-based screening policies. For immigrants, <10% of parameter combinations predicted TBI entry screening to be more cost-effective than CXR screening under observed TPT completion rates (36%). However, this changed to nearly 100% of parameter combinations for immigrants coming from countries with a TB incidence of ≥100 per 100,000 when applying TPT completion rates as observed in asylum seekers (72%). For asylum seekers, 100% of parameter combinations predicted cost-effectiveness, while 0% predicted TBI screening to be cost-effective among settled migrants. - Conclusions - TBI entry screening is a cost-effective alternative to CXR entry screening for immigrants and asylum seekers coming from high TB endemic countries, provided TPT completion is sufficiently high.